Simultaneous quantitative analysis of phosphocreatine, creatine and creatinine in plasma of children by HPLC–MS/MS method: Application to a pharmacokinetic study in children with viral myocarditis. (17th May 2019) - Sun, Ning; Li, Qirui; Zhao, Libo; He, Huan; Zhang, Meng; Wang, Xiaoling
Abstract: A simple and rapid HPLC–MS/MS method was developed and validated for simultaneous measurement of phosphocreatine and its metabolites creatine and creatinine in children's plasma. A 50 μL aliquot of plasma was prepared by protein precipitation with acetonitrile–water (1000 μL, 1:1, v/v) followed by separation on a Hypersil Gold C18 column (35°C) with gradient mobile phase consisting of 2 mm ammonium acetate aqueous solution (pH 10) and methanol at a flow rate of 0.3 mL/min and analyzed by mass spectrometry in both positive (phosphocreatine) and negative (creatine and creatinine) ion multiple reaction monitoring mode. Good linearity ( r > 0.99) was obtained for the three analytes. The intra‐day and inter‐day values of CV were <5.46% (−13.09% ≤ RE ≤ 2.57%). The average recoveries of the three analytes were 70.9–97.5%. No obvious impact was found for the quantitation of three analytes in normal, hemolyzed and hyperlipemic plasma. In the end, this method was successfully applied to a pharmacokinetic study of phosphocreatine in children (six cases) with viral myocarditis of children after intravenous infusion of 2 g of the test drug. The pharmacokinetc parameters of phosphocreatine/creatine were as follows: t 1/2 0.24/0.83 h, T max 0.49/0.55 h, C max 47.34/59.29 μg/mL, AUClast 17.07/59.63 h μg/mL, AUCinf 17.16/79.01 h μg/mL and MRT 0.29/0.67 h.